2013
DOI: 10.1016/j.cyto.2012.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of ferret CCL20 and CCR6 and identification of chemotactic inhibitors

Abstract: CCL20 is currently the only known chemokine ligand for the receptor CCR6, and is a mucosal chemokine involved in normal and pathological immune responses. Although nucleotide sequence data are available for ccl20 and ccr6 sequences from multiple species, the ferret ccl20 and ccr6 sequences have not been determined. To increase our understanding of immune function in ferret models of infection and vaccination, we have used RT-PCR to obtain the ferret ccl20 and ccr6 cDNA sequences and functionally characterize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Chemotaxis assay was performed using murine L1.2 cells engineered to express ferret CCR6 as described (Qin et al, 2013). Briefly, a total of 200,000 of L1.2.fCCR6 responder cells were loaded on top of the porous membrane (ChemoTx ® Disposable Chemotaxis System, pore size 5 µm, NeuroProbe) in triplicate and incubated at 37°C/5% CO 2 for 2 hr in a humid chamber.…”
Section: Chemotaxismentioning
confidence: 99%
See 2 more Smart Citations
“…Chemotaxis assay was performed using murine L1.2 cells engineered to express ferret CCR6 as described (Qin et al, 2013). Briefly, a total of 200,000 of L1.2.fCCR6 responder cells were loaded on top of the porous membrane (ChemoTx ® Disposable Chemotaxis System, pore size 5 µm, NeuroProbe) in triplicate and incubated at 37°C/5% CO 2 for 2 hr in a humid chamber.…”
Section: Chemotaxismentioning
confidence: 99%
“…Chemotactic index (CI) was calculated relative to control wells with no chemokine. Chemically synthesized ferret CCL20 (Qin et al, 2013) was used as a control.…”
Section: Chemotaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have identified cross-reactive antibodies that recognize populations of ferret leukocytes, such as CD8, CD11␤, CD44 and CD25, and cytokines IFN␥, TNF␣, IL4 and IL8 (Rutigliano et al, 2008;Martel and Aasted, 2009;Pillet et al, 2011). Cloning and sequencing of ferret cytokine genes have enabled molecular approaches targeting the corresponding mRNAs (von Messling et al, 2006;Danesh et al, 2008;Nakata et al, 2008;Ochi et al, 2008;Qin et al, 2013). Expression of cytokine and chemokine genes has been assessed in ex vivo samples following infection of naïve or vaccinated ferrets with influenza virus or SARS-CoV by microarray analysis Fang et al, 2010;Rowe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, CCR6 is highly expressed in Tregs, which suppress immune responsiveness (Kleinewietfeld et al, 2005;Frick et al, 2013;Li et al, 2013). Chemokine (C-C motif) ligand 20 (CCL20) is a chemokine ligand known to attract CCR6 + -expressing cells by inducing migration (Marsigliante et al, 2013) and binding to endothelial cells (Qin et al, 2013). Their role in inducing immune tolerance in pregnancy has drawn increased attention recently.…”
Section: Introductionmentioning
confidence: 99%